2021
DOI: 10.3390/nu13020602
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Novel Immunomodulatory Effects of L-Sulforaphane

Abstract: The dietary isothiocyanate L-sulforaphane (LSF), derived from cruciferous vegetables, is reported to have several beneficial biological properties, including anti-inflammatory and immunomodulatory effects. However, there is limited data on how LSF modulates these effects in human immune cells. The present study was designed to investigate the immunomodulatory effects of LSF (10 µM and 50 µM) on peripheral blood mononuclear cell (PBMC) populations and cytokine secretion in healthy adult volunteers (n = 14), in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
4
9
0
Order By: Relevance
“…SF demonstrated anti-inflammatory and anti-oxidative activities as demonstrated previously [ 87 89 ]. SF was capable of reducing both IL-1β and IFN-γ levels, this run in agreement with several studies [ 90 93 ], signifying the role of SF as an antioxidant bioactive molecule with anti-inflammatory potential.…”
Section: Discussionsupporting
confidence: 92%
“…SF demonstrated anti-inflammatory and anti-oxidative activities as demonstrated previously [ 87 89 ]. SF was capable of reducing both IL-1β and IFN-γ levels, this run in agreement with several studies [ 90 93 ], signifying the role of SF as an antioxidant bioactive molecule with anti-inflammatory potential.…”
Section: Discussionsupporting
confidence: 92%
“…These findings were consistent in all four samples. Genes encoding for the expression of cytokines and chemokines such as IL-6, IL-1A, IL-1B, EB13, CXCL5, and CXCL1, were primarily downregulated, highlighting the anti-inflammatory signature of LSF 23,36,38 .…”
Section: Our Findings Indicated Reductions Of Inflammatory Infiltrate...mentioning
confidence: 99%
“…A limitation of our study is that the potential effects of key SFN metabolites were not explicitly investigated. We have recently shown that although not as potent as LSF, metabolites such as SFN-Cys and SFN-NAC, have important roles in anti-inflammatory pathways 23 . Here, we show acetylation of -tubulin following in vivo administration of LSF (Fig 6).…”
Section: Our Findings Indicated Reductions Of Inflammatory Infiltrate...mentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the therapeutic options for bladder cancer have been considerably widened by the introduction of immune checkpoint inhibitors targeting cytotoxic T lymphocyte antigen 4 (CTLA4) and programmed death (ligand) 1 (PD-1/PDL1). In view of these new treatment modalities aimed at suppressing tumor cell inhibition of anticancer immune responses [ 117 ], it has become evident that SFN may exert immunomodulatory effects by altering the proportion of natural killer cells, monocytes, dendritic cells, T- and B-cells [ 118 ]. Investigation of human peripheral blood T-cells derived from healthy donors showed that SFN induces a significant accumulation of ROS in the T-cells, which resulted in the inhibition of T-cell activation and T-cell effector functions [ 119 ].…”
Section: Sfn In Bladder Cancermentioning
confidence: 99%